MORPHOLOGICAL CHARACTERISTIC OF VIERUL LOCAL GRAPE (Vitis spp.) CUTTING SEEDS ON PODZOLIC SOIL USING VARIOUS CONCENTRATION OF AUXIN SOAK - Fitria Nugraheni Sukmawati; Saktiyono Sigit Tri Pamungkas; Tusrianto Tusrianto; Alfu Laila; Yudhi Pramudya (Agric, 2023)
The development of grapes (Vitis vinifera) has obstacle among others are limited optimal land and difficult nurseries. Suboptimal land use for grape cuttings can use red yellow podzolic soil (ultisol). Podzolic soil has an acidic pH and low macro and micro nutrient uptake but can still be used as a growing medium. Vierul local grapes are a type of grape that has begun to be developed as root stock in nurseries but needs to be improved for its root success using a synthetic phytohormones bath of napthaline acetic acid (NAA). The purpose of this study was to determine the morphological character of vierul local grape cuttings at various concentrations of NAAsoaking in podzolic soil growing medium. This research has been carried out in a screen house from August to December 2021. This study used a non-factorial completely randomized design (CRD) with 3 treatments and 3 replications as block consisting of F0, F1, F2, F4 following by 0, 2, 4, 6 g L-1 respectively. The morphological characteristics observed is number of bud break, time of leaves appear, number of leaves, tendril length and percentage of live cuttings. The results of the study were analyzed using ANOVA at the 5% level and continued using the DMRT at the 5% level. The result showed that soaking of NAA at a concentration of 0 g L-1 (F0) had the best result for the variable number of bud break and number of leaves. Concentration of 6 g L-1 (F3) had the best result for variable length of the tendril while for the variable when the leaves appear, NAA soaking has no significant effect. The percentage of live cuttings is still low because it is influenced by the quality (material) of cuttings, the age of woodstock, growing media and water availability.